Pemikiran Ekonomi Ibn Qayyim al-Jawziyyah - Borhan, Joni Tamkin (Jurnal Usuluddin, 2007)
This article explains about the contribution and economic thought of Ibn Qayyim al-Jawziyyah, a great Muslim thinker in the 13/14th century. His contributions and thought were about the principles of Islamic economics, concept of riches and poverty, economic of zakat, concept of interest, marketing mechanism and price regulation. His thought in economics was mainly to realize the concept of social welfare, establishment of justice and elimination of injustice in economic life.